Pengaruh Penambahan Probiotik dalam Pakan terhadap Pertambahan Berat Badan, Konsumsi Pakan dan Konversi Pakan Ayam Broiler - Yovita Florida Seran; Charles V. Lisnahan; Theresia I. Purwantiningsih (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
This study aimed to determine the effect of pro-bio addition in the feed to weight gain, feed consumption, and feed conversion of broilers. This study was carried out in the cage’s of the Animal Husbandry Study Program, Faculty of Agriculture, Timor University from September to November, 2018. A total 80 day-old broilers (DOC) were used in the study.The feed utilized were BR1, BR2 and pro-bio. The experiment was designed as a Complete Randomized Design (CRD) consisting of 4 treatments and 4 replications. The treatments consisted of P0 (commercial feed without probio), P1 (99,7% commercial feed +0.3% probio), P2 (99,5% commercial feed +0.5% probio) and P3 (99.3% commercial feed + 0,7% probio). The variables observed were weight gain, feed consumption, and feed conversion. The data of weight gain of P0, P1, P2 and P3 were 49,05; 52,53; 48,80 and 53,42 g/bird/day, respectively. The feed consumption were 134,74; 137,21; 138,16 and 139,52 g/bird/day, respectively. The feed conversion were 2,75; 2,62; 2,83 and 2,61, respectively. The results of the statistical analysis showed that the addition of pro-bio had a very significant effect (P<0.01) on feed consumption, whereas weight gain and feed conversion had not significant effect. It was concluded that the addition of probiotics in feed had no effect on weight gain, feed conversion but could have a significant effect on feed consumption.